2022
DOI: 10.3389/fdgth.2022.976566
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals knowledge of telemedicine and its associated factors working at private hospitals in resource-limited settings

Abstract: IntroductionThe appropriate implementation of telemedicine in the healthcare system has the potential to overcome global problems such as accessibility and quality healthcare services. Thus assessing the knowledge of health professionals before the actual adoption of telemedicine is considered a prominent solution to the problems.ObjectiveThis study aimed to assess healthcare professionals' knowledge of telemedicine and its associated factors at private hospitals in low-resource settings.MethodAn institution-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Pharmacy students who took training on a basic computer were 2.00 times more likely to have adequate knowledge of Tele-pharmacy than students who did not receive basic computer training. This study's findings are consistent with previous research indicating that computer training can improve understanding of the Telehealth applications [ 30 – 32 ]. This is because basic computer training is the most critical factor in improving students' knowledge of Tele-pharmacy [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Pharmacy students who took training on a basic computer were 2.00 times more likely to have adequate knowledge of Tele-pharmacy than students who did not receive basic computer training. This study's findings are consistent with previous research indicating that computer training can improve understanding of the Telehealth applications [ 30 – 32 ]. This is because basic computer training is the most critical factor in improving students' knowledge of Tele-pharmacy [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…The successful adoption and utilization of emerging digital technologies require adequate education and training for healthcare providers and patients. Healthcare providers should be proficient in using these technologies effectively, while patients need to be educated about the benefits, risks, and privacy considerations related to the use of digital tools [61][62][63].…”
Section: Provider and Patient Educationmentioning
confidence: 99%
“…On the contrary, a study conducted on referral hospitals of the Amhara region, North West Ethiopia indicates that the proportion of health professional's knowledge of telemedicine is sufficient but not enough [14,17]. Studies found that having IT support staff, Socio-demographic factors (gender, residence), Internet availability in the workplace, information sharing culture, computer training, and computer literacy skills are interlinked to knowledge of telemedicine [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%